A conserved truncated isoform of the ATR-X syndrome protein lacking the SWI/SNF-homology domain. - Garrick, D; Samara, V; McDowell, T; Smith, A; Dobbie, L; Higgs, D; Gibbons, R (2004)
Mutations in the ATRX gene cause a severe X-linked mental retardation syndrome that is frequently associated with alpha thalassemia (ATR-X syndrome). The previously characterized ATRX protein (approximately 280 kDa) contains both a Plant homeodomain (PHD)-like zinc finger motif as well as an ATPase domain of the SNF2 family. These motifs suggest that ATRX may function as a regulator of gene expression, probably by exerting an effect on chromatin structure, although the exact cellular role of ATRX has not yet been fully elucidated. Here we characterize a truncated (approximately 200 kDa) isoform of ATRX (called here ATRXt) that has been highly conserved between mouse and human. In both species, ATRXt arises due to the failure to splice intron 11 from the primary transcript, and the use of a proximal intronic poly(A) signal. We show that the relative expression of the full length and ATRXt isoforms is subject to tissue-specific regulation. The ATRXt isoform contains the PHD-like domain but not the SWI/SNF-like motifs and is therefore unlikely to be functionally equivalent to the full length protein. We used indirect immunofluorescence to demonstrate that the full length and ATRXt isoforms are colocalized at blocks of pericentromeric heterochromatin but unlike full length ATRX, the truncated isoform does not associate with promyelocytic leukemia (PML) nuclear bodies. The high degree of conservation of ATRXt and the tight regulation of its expression relative to the full length protein suggest that this truncated isoform fulfills an important biological function.